Blastocystis spp Infections Among Inhabitants of a Low Income Community of Niterói, Rio de - Adami, Yara Leite (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
Blastocystis spp is an anaerobic enteric protozoan food-borne parasitethat remains, until nowadays, subject of controversy. In fact, little is known about its pathogenic potential, genetic diversity, host-parasite interactions and treatment (Kayaet al.; 2007; Tan, 2008). Actually, it is the most frequently found enteroparasite incoproparasitological research and have been implicated in affections such as irritablebowel syndrome, but epidemiological studies are inconclusive (Nagel et al.; 2015).Indeed, some studies have inferred the existence of prevalence rates around 50% indeveloping countries, while in drops to 1.5-10% in developed world. These high taxain developing countries is due, mainly, to precarious living conditions and social andeconomical factors suggesting that transmission increases in communities where basicsanitation is scarce, continuous use of sources of untreated water and contact withdomestic animals. Infections by Blastocystis spp are detected in faecal samples fromassymtomatic and symptomatic individuals and in some epidemiological studies,infected people report abdominal pain, diarrhoea, nausea, vomitus, bloating, anorexiaand dermatological manifestations (Kurt et al.; 2016).The protozoan is pleomorphic and at least four different forms have been reported anddescribed (Tan, 2008). Besides, some advances on the biology of the parasite havebeen achieved as molecular studies based on polimerase chain reaction (PCR) showedthat it has – until now – 17 different subtypes and nine of them able to cause humaninfection. However, despite Blastocystis spp isolates from humans and animals havebeen reported to be morphologically similar, human beings are frequently infected bysubtypes ST1- ST9 (Tan, 2008; Sandpool et al.; 2017).The parasite can be detected through coproparasitological techniques and is verycommon in fresh faecal samples from inhabitants of low income communities